2014
DOI: 10.1063/1.4895781
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity dynamics for transient high-pressure liquid injection

Abstract: The liquid jet from a round orifice during the transient start-up and steady mass flux periods of a high pressure injector is studied via Navier-Stokes and level-set computations. Via post-processing, the role of vorticity dynamics is examined and shown to reveal crucial new insights. A brief review of relevant literature is made. An unsteady, axisymmetric full-jet case is solved. Then, a less computationally intensive case is studied with a segment of the jet core undergoing temporal instability; agreement wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 57 publications
13
69
0
Order By: Relevance
“…Recent ballistic images, near the nozzle of diesel-like sprays at high pressure, high Re and We by Duran, Porter & Parker (2015) show that the cone angle increases with ambient pressure; see figure 2. They found resemblance between the sizes of their observed structures and the previous computational results of Jarrahbashi & Sirignano (2014), hereinafter cited as JS. However, more studies are required to delineate the liquid structures before final break up into droplets.…”
supporting
confidence: 70%
“…Recent ballistic images, near the nozzle of diesel-like sprays at high pressure, high Re and We by Duran, Porter & Parker (2015) show that the cone angle increases with ambient pressure; see figure 2. They found resemblance between the sizes of their observed structures and the previous computational results of Jarrahbashi & Sirignano (2014), hereinafter cited as JS. However, more studies are required to delineate the liquid structures before final break up into droplets.…”
supporting
confidence: 70%
“…An explicit first-order timeintegration scheme is used instead of high-order explicit approaches or implicit methods [14] to discretize Eqs. (4) and (5). Since we are interested in the early stages of flow evolution, the small time step restriction does not become a critical point of the numerical solution.…”
Section: Discretization Of the Equationsmentioning
confidence: 99%
“…The main focus of these studies has been on understanding and relating vortex stretching [7], vortex tilting [8], and baroclinic effects [9] to the appearance of three-dimensionality in liquid jet instabilities. Earlier experimental studies in this field [6,[8][9][10][11][12][13][14] have been followed and reproduced in more detail by numerical computations [1,4,5,[15][16][17][18][19][20][21]. In the first studies of the role of streamwise vorticity for round liquid jets flowing into a gas, Jarrahbashi and Sirignano [4] and Jarrahbashi et al [5] showed how the mechanisms of the formation of lobes and ligaments are related to the growth of streamwise vorticity.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity decays exponentially to zero at the center of the liquid sheet. For more detailed description of the initial conditions, see Zandian et al [22] Grid independency and domain-size independency tests have also been performed [4,5,22]. The liquid-gas interface is initially perturbed symmetrically on both sides with a sinusoidal profile and predefined wavelength and amplitude obtained from 2D full-jet simulations [22].…”
Section: Numerical Modelingmentioning
confidence: 99%
See 1 more Smart Citation